2014
DOI: 10.1016/j.actbio.2014.03.032
|View full text |Cite
|
Sign up to set email alerts
|

A review on the wettability of dental implant surfaces II: Biological and clinical aspects

Abstract: Dental and orthopaedic implants have been under continuous advancement to improve their interactions with bone and ensure a successful outcome for patients. Surface characteristics such as surface topography and surface chemistry can serve as design tools to enhance the biological response around the implant, with in vitro, in vivo and clinical studies confirming their effects. However, the comprehensive design of implants to promote early and long-term osseointegration requires a better understanding of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
504
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 659 publications
(537 citation statements)
references
References 125 publications
21
504
2
10
Order By: Relevance
“…The superposition of nanoscale structures (pore diameter ranged between 20 nm and 180 nm) on a microrough surface (Sa=2.20) has been reported to provide the original surface with additional benefits including the enhancement of osteogenic gene expression 46) and modification of the expression profile of integrin subunits 47) of osteoblasts. Wettability has also been identified as an important factor affecting the control of osteogenic cell differentiation 48,49) . However, it is usually difficult to evaluate the specific contribution of wettability because wettability is strongly affected by the surface roughness and chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superposition of nanoscale structures (pore diameter ranged between 20 nm and 180 nm) on a microrough surface (Sa=2.20) has been reported to provide the original surface with additional benefits including the enhancement of osteogenic gene expression 46) and modification of the expression profile of integrin subunits 47) of osteoblasts. Wettability has also been identified as an important factor affecting the control of osteogenic cell differentiation 48,49) . However, it is usually difficult to evaluate the specific contribution of wettability because wettability is strongly affected by the surface roughness and chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Recent attempts to modify wettability without changing the surface microstructure and chemistry have revealed that hydrophilic surfaces modulated the expression profile of integrin subunits and enhanced osteogenic cell differentiation 50,51) . The hypothetical mechanism of the effects of hydrophilic surfaces on cell attachment and subsequent reactions is that the hydrophilicity influences the protein absorption to the material surface and prevents the entrapment of air bubbles within the surface architecture, which could interfere with protein absorption and materialcell interaction 49) . Increased wettability resulting from the bioactive treatment might have been especially beneficial for the SLM-T materials evaluated in this study, because materials fabricated by SLM have very rough surfaces and a complex architecture that might increase the risk of entrapment of air bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations on the dental implant surface focus on mimicking the bone's hierarchical structures due to the formation of bioactive, hydrophilic layers at the micro and/or nanoscale. It was reported that the contact angle of medical dental implants ranges from value near 0 • (superhydrophilic) to near 150 • (superhydrophobic) [31]. According to Gittens at al., surface wettability affects (i) the adhesion of proteins and other macromolecules, (ii) hard and soft tissue cell interactions, (iii) bacterial adhesion and biofilm formation, and (iv) the rate of the osseointegration in in vivo conditions.…”
Section: Wettability and Surface Roughnessmentioning
confidence: 99%
“…A principal property of the surface with biological implications is wettability feature [23]. Still more information is needed to completely understand the effects of wettability on cell attachment and tissue integration.…”
Section: Surfaces For Cell Proliferation and Differentiationmentioning
confidence: 99%
“…Surprisingly for dental Table showing the strength of attachment to porcine intestine tissue between non nanotextured and textured with and without oxidised dextran [22] implants the wettability is usually not measured or considered in biological evaluation. The topic has been scrutinised most widely for implant osseointegration [23]. Generally wettabilities of intermediate values can optimise favourable cell interactions.…”
Section: Surfaces For Cell Proliferation and Differentiationmentioning
confidence: 99%